Beta‐lactam resistance and the effectiveness of antimicrobial peptides against KPC‐producing bacteria. Issue 7 (30th August 2022) - da Costa de Souza, Guilherme; Roque‐Borda, Cesar Augusto; Pavan, Fernando R.
Abstract: Bacterial resistance is a problem that is giving serious cause for concern because bacterial strains such as Acinetobacter baumannii and Pseudomonas aeruginosa are difficult to treat and highly opportunistic. These bacteria easily acquire resistance genes even from other species, which confers greater persistence and tolerance towards conventional antibiotics. These bacteria have the highest death rate in hospitalized intensive care patients, so strong measures must be taken. In this review, we focus on the use of antimicrobial peptides (AMPs) as an alternative to traditional drugs, due to their rapid action and lower risk of generating resistance by microorganisms. We also present an overview of beta‐lactams and explicitly explain the activity of AMPs against carbapenemase‐producing bacteria as potential alternative agents for infection control.